2015
DOI: 10.1001/jamasurg.2015.2202
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Metabolic Effects of Laparoscopic Sleeve Gastrectomy

Abstract: Undergoing LSG induced efficient weight loss and a major improvement in obesity-related comorbidities, with mostly no correlation to percentage of excess weight loss. There was a significant weight regain and a decrease in remission rates of diabetes and, to a lesser extent, other comorbidities over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(66 citation statements)
references
References 43 publications
2
56
2
5
Order By: Relevance
“…At 10 years, 8.8% of RYGB patients and 25.0% of AGB patients had lost less than 5% of their original weight, , and at 15 years postsurgery, RYGB patients had regained an average 5% from their highest weight loss and AGB patients had regained 7%. Golomb et al reported similar regain and weight loss failure in VSG, with average excess weight loss of 76.8% at 1 year, 69.7% after 3 years and 56.1% at 5 years postsurgery, and excess weight loss of <50% at 13.3% at 1 year, 21.1% at 3 years and 38.5% at 5 years. Multiple determinants, including biological, surgical, social, behavioural and psychological factors such as problematic and disordered eating behaviours, have been linked to poor weight loss and weight regain .…”
Section: Discussionmentioning
confidence: 80%
“…At 10 years, 8.8% of RYGB patients and 25.0% of AGB patients had lost less than 5% of their original weight, , and at 15 years postsurgery, RYGB patients had regained an average 5% from their highest weight loss and AGB patients had regained 7%. Golomb et al reported similar regain and weight loss failure in VSG, with average excess weight loss of 76.8% at 1 year, 69.7% after 3 years and 56.1% at 5 years postsurgery, and excess weight loss of <50% at 13.3% at 1 year, 21.1% at 3 years and 38.5% at 5 years. Multiple determinants, including biological, surgical, social, behavioural and psychological factors such as problematic and disordered eating behaviours, have been linked to poor weight loss and weight regain .…”
Section: Discussionmentioning
confidence: 80%
“…However, adverse effects of some and the transient weight losses associated with others[27] mean that the pharmacological management of obesity remains suboptimal. The only proven treatment to achieve and maintain weight loss in obesity is bariatric surgery[28-30]. However, surgical and anaesthetic risks associated with overweight and obese status sees these invasive procedures reserved to those patients classed morbidly obese (BMI ≥ 40 kg/m 2 ) or as a last resort in those failing more conservative management[20,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Although Golomb et al had retrospectively doubted the dominant role of bariatric surgery at 5-year follow-up [38], its contrastive efficacy against non-surgical interventions remains advantageous according to our pooled analysis, especially concerning the long-term durability of weight loss and hyperglycemic remission. It is experimentally explanatory that physiological adaptation instead of mechanical reconstruction seems to mainly contribute to the prolonged impacts on energy homeostasis.…”
Section: Discussionmentioning
confidence: 84%